Clinical development of the oral gonadotropin-releasing hormone antagonist elagolix - Kristof Chwalisz, M.D., Ph.D. (F&S Reports, 2023)
Elagolix is the first oral gonadotropin-releasing hormone antagonist that entered clinical development and received regulatory approval for the management of women with endometriosis and heavy menstrual bleeding associated with uterine fibroids in combination with a hormonal add-back therapy. This mini review aims to summarize the key clinical studies that led to its regulatory approval.